1998
DOI: 10.1136/bmj.317.7163.905
|View full text |Cite
|
Sign up to set email alerts
|

Geographical variation in anophthalmia and microphthalmia in England, 1988-94   Commentary: Clustering of anophthalmia and microphthalmia is not supported by the data

Abstract: Objective: To investigate the geographical variation and clustering of congenital anophthalmia and microphthalmia in England, in response to media reports of clusters. Design: Comparison of pattern of residence at birth of cases of anophthalmia and microphthalmia in England in 1988-94, notified to a special register, with pattern of residence of all births. Three groups studied included all cases, all severe cases, and all severe cases of unknown aetiology. Outcome measures: Prevalence rates of anophthalmia an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…This study simulated conditions that could reasonably occur in public health settings, which usually have a few thousand observations [ 15 17 ]. Additionally, with the move towards “big data” by government organizations [ 18 ] and industry, both the number of observations and the size of the areas being routinely studied could increase substantially.…”
Section: Resultsmentioning
confidence: 99%
“…This study simulated conditions that could reasonably occur in public health settings, which usually have a few thousand observations [ 15 17 ]. Additionally, with the move towards “big data” by government organizations [ 18 ] and industry, both the number of observations and the size of the areas being routinely studied could increase substantially.…”
Section: Resultsmentioning
confidence: 99%
“…Dolk et al [ 6 ] reported that prevalence of anophthalmia is extremely low, i.e. around 3/100,000 births.…”
Section: Discussionmentioning
confidence: 99%
“…Anophthalmia has also been related to environmental factors like maternal vitamin A deficiency, solvent use or exposure to X-rays, or to drugs like thalidomide, warfarin or alcohol [ 6 ]. We do not think any of these was the cause of anophthalmia, since the mother was not exposed to the referred risks and did not present clinical findings related to vitamin A deficiency along pregnancy, like blurred vision, nocturnal blindness or corneal ulcers [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nonconservative missense mutations in SUFU (orthologous to the gene mutated in the zebrafish dre mutants) have been observed in independently isolated medulloblastomas [73] and are therefore associated with cancer. Geographical clusters of children with eye malformations, born to unaffected parents, and the increased incidence of some cancers in certain areas suggest that environmental factors may be implicated in these diseases [74,75]. Might such factors play their role by affecting the penetrance of underlying mutations or deleterious polymorphisms in susceptible individuals through diversion of Hsp90 function?…”
Section: Discussionmentioning
confidence: 99%